Point Prevalence and Associated Factors of Hip Displacement in Pediatric Patients With Mitochondrial Disease - Kim, Sungmin; Lee, Young-Mock; Park, Kun-Bo; Lee, Minsu; Park, Hoon (Frontiers in Pediatrics, 2021)
Objective: Mitochondrial disease is a multisystem disorder resulting from mitochondrial dysfunction. Although musculoskeletal system is vulnerable to mitochondrial dysfunction, little information is available on orthopedic issues such as hip displacement and scoliosis in patients with mitochondrial disease. We aimed to examine the point prevalence of hip displacement and investigate the associated factors in patients with mitochondrial disease. Methods: We retrospectively reviewed the medical records and plain radiographs of patients diagnosed with mitochondrial disease between January 2006 and January 2019 at a single institution. Data, including patient age, sex, follow-up duration, syndromic diagnosis, and gross motor function were collected. Migration percentage was measured on the radiographs. The clinical and radiologic variables were compared between patients classified according to the presence of hip displacement and motor function level. Results: We included 225 patients (135 men, 90 women). The mean age at the latest follow-up was 11.1 years, and the mean follow-up duration was 7.0 years. Hip displacement was noted in 70 (31.1%) patients. The proportion of patients with Leigh disease (p = 0.007) and the ratio of non-ambulators (p < 0.001) were higher among patients with hip displacement. The proportion of patients with Leigh disease was higher in the non-ambulators than the ambulators. Conclusion: One-third of patients with mitochondrial disease developed hip displacement. Hip displacement was more common in non-ambulators or patients with hypertonia. Careful and serial monitoring for hip problems is required for non-ambulatory patients with mitochondrial disease who have increased muscle tone.